Efektivitas Intervensi Peer Education sebagai Strategi Pencegahan Pergaulan Bebas pada Mahasiswa di Perguruan Tinggi - Sriyana Sriyana; Effrata Effrata; Silvia Arianti; Resviya Resviya; Rosmawiah Rosmawiah (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aims to examine the effectiveness of peer education-based counseling in preventing risky social behavior among university students at Universitas PGRI Palangka Raya. A quantitative approach with a pre-experimental one-group pretest–posttest design was employed, involving 50 students selected through purposive sampling. Data were collected using questionnaires, observation, and documentation, and analyzed using descriptive statistics. The findings revealed a significant improvement in students’ knowledge and attitudes after the intervention. The mean score increased from 59.86 (pre-test) to 81.74 (post-test), indicating an overall improvement of approximately 36.6%. In addition, knowledge increased by 24% and attitudes by 22%. These results demonstrate that peer education is highly effective due to social proximity, interactive learning methods, and peer influence. However, several challenges were identified, including limited time, varying levels of participant understanding, and limited learning facilities. Overall, this study highlights the potential of peer education as a sustainable and participatory strategy for preventing risky behavior in higher education settings.